ISLAM DAN NEGARA : Metamorfosa Pemikiran Politik Islam Indonesia - Agus Riyanto (SPEKTRUM, 2004)
Abstract The relation of Islam and state is still as conflictual issue in recent decade, and interest topic to be explored. The development of Islam and state relation discourse does not exclude from political thinking synthesis, include of them are Islamic scholar and leader in Indonesia. The article describes how Indonesian Islamic political thinking metamorphosis, especially on Islam and state relation, since pre-national independence until reformation era. Key words : Islam, state, politics